Creature Symbols to Foreshadow Harrys Confrontation with his Past in J.K. Rowlings Harry Potter and the Prisoner of Askaban - Fabian Firman Elmar; Maria Ananta (Universitas Sanata Dharma, 2017)
Symbol is a major element in literary works. It always has a meaning which is different than the literal meaning of the symbol itself, and thus, it is prevalent in literary works which often contain hidden meanings. Foreshadowing on the other hand, is the act of vaguely hinting the readers to the future event in the story or even the outcome of said story. This study discusses the creature symbols presented in J.K. Rowlings Harry Potter and the Prisoner of Azkaban as foreshadowing element that hints towards the confrontation between Harry and his past in the conflict of the novel. There are three creature symbols found in the novel: The black dog, the rat Scabbers, and the dementors of Azkaban. The black dog reflects Sirius loyalty to his friends and its black fur symbolizes the sorrow and mourning he felt for their death, but its resemblance with the Grim stands for his vengeful obsession to Peter Pettigrew whom had betrayed him and the Potters. The rat Scabbers on the other hand, symbolizes betrayal, cowardice, and cunning trickery, traits that can be found in Peter Pettigrew. The dementors meanwhile, symbolizes hopeless misery and despair known as depression. These guardians of Azkaban foreshadowed that the conflict would be a confrontation between Harry and his past while the black dog and rat revealed the truth behind said past regarding who betrayed the Potters twelve years ago and the innocent man whom said crime was blamed upon.Key words: symbols, foreshadow, J.K. Rowling